Choroby wątroby i nerek w przebiegu ciliopatii - Lipiński, Patryk; Jankowska, Irena; Grenda, Ryszard (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Ciliopathies constitute a group of disorders characterized by cilia abnormalities and an extremely heterogeneous clinical presentation. The liver and kidneys are the most commonly affected organs and the term hepatorenal ńbrocystic disorders is used to describe ciliopathies with combined liver and kidney involvement. Liver disorders in ciliopathies can be grouped into three categories: congenital hepatic ńbrosis, Caroli's disease and polycystic liver disease. Kidney disorders related to primary cilia abnormalities include autosomal dominant and recessive polycystic kidney diseases and nephronophthisis.